Apollo, Kronos’s Avenger? Divine Intergenerational Conflicts in Light of ‘The Curse of Kronos’ (Prometheus Bound 907‒12) - Paprocki, Maciej (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2025)
Within the Greek mythos, supremacy among the gods passes down from father to son in a series of coups, from Ouranos to Kronos to Zeus; Zeus faces many pretenders to his throne but evades the fate of his father. The following article examines ancient Greek texts that represent Apollo as Zeus’s potential successor. I read references to Apollo’s unruliness against the so-called curse of Kronos (ἀρὰ Κρόνου, Prometheus Bound 907‒12). I argue that analyzed texts insinuate that Apollo could have avenged his grandfather and restarted the divine succession, a notion reframed by different authors to give Zeus another worthy challenger.